Negative active material, preparation method thereof and lithium ion battery

By forming a double cladding layer of inorganic lithium salt and lithium sulfonate on the graphite surface, the problem of the improvement of the fast charging performance of the negative electrode active material in the prior art is solved, and efficient lithium ion embedding and rate performance improvement is achieved.

CN119852361AInactive Publication Date: 2025-04-18HUBEI SNOW NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510036401.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art leads to the problem of reducing energy density and its first-time efficiency reduction when improving the fast charging performance of negative electrode active materials.

Method used

A negative electrode active material is used, including graphite as the core, an inorganic lithium salt as the first cladding layer, and lithium sulfonate as the second cladding layer, and a uniform and dense cladding layer is formed by a specific preparation method, including carbonization treatment and electrochemical deposition.

Benefits of technology

Through the high conductivity of inorganic lithium salt and the good electrolyte compatibility of lithium sulfonate, the interface resistance is reduced, the charging and discharging efficiency of the battery is improved, the intercalation and detachment rate of lithium ions is enhanced, the conduction path of lithium ions is optimized, and the rate performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852361A_ABST
    Figure CN119852361A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode active material, a preparation method thereof and a lithium ion battery, and relates to the technical field of battery materials, the negative electrode active material comprises an inner core, a first coating layer at least partially coating the inner core, and a second coating layer at least coating the first coating layer; wherein the inner core comprises graphite, the first coating layer comprises inorganic lithium salt, and the second coating layer comprises lithium sulfonate. According to the technical scheme, the problems that the energy density of the negative electrode active material is reduced and the first efficiency is reduced when the fast charging performance of the negative electrode active material is improved in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery material preparation, and in particular to a negative electrode active material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Currently, fast-charging graphite is primarily composed of graphite and its outer layer of soft carbon and hard carbon materials. Due to the consumption of lithium ions during the initial charge and discharge process, the initial efficiency of the material and the lithium ion transfer rate are reduced. While there are many ways to improve the fast-charging performance of graphite, such as reducing the particle size and increasing the amount of amorphous carbon coating, these methods will result in a decrease in energy density and a decrease in initial efficiency. Summary of the Invention

[0003] The main purpose of the present invention is to propose a negative electrode active material, a preparation method thereof and a lithium ion battery, aiming to solve the problem in the prior art of reducing the energy density of the negative electrode active material and reducing its initial efficiency when improving the fast charging performance of the negative electrode active material.

[0004] In order to achieve the above technical objectives, the present invention also proposes a negative electrode active material, comprising a core, a first coating layer that at least partially covers the core, and a second coating layer that at least covers the first coating layer; wherein the core comprises graphite, the first coating layer comprises an inorganic lithium salt, and the second coating layer comprises lithium sulfonate.

[0005] In one embodiment, the invention further comprises a coupling agent layer, wherein the coupling agent layer is located between the first coating layer and the second coating layer, and the coupling agent layer comprises a titanate coupling agent.

[0006] The present invention also provides a method for preparing a negative electrode active material, comprising the following steps:

[0007] S100, providing graphite oxide, mixing the graphite oxide, an inorganic lithium salt, a dispersant, and a first solvent, and performing a carbonization treatment to obtain a first precursor material;

[0008] S200, depositing lithium sulfonate on the surface of the first precursor material by an electrochemical method to obtain the negative electrode active material;

[0009] The negative electrode active material includes a core, a first coating layer that at least partially covers the core, and a second coating layer that at least covers the first coating layer; the core includes graphite, the first coating layer includes an inorganic lithium salt, and the second coating layer includes lithium sulfonate.

[0010] In one embodiment, step S100 includes:

[0011] Providing graphite oxide, mixing an inorganic lithium salt, a dispersant, and a first solvent to obtain a first solution, dispersing the graphite oxide in the first solution, and performing a carbonization treatment to obtain a first precursor material;

[0012] Wherein, in the first solution, the mass proportion of the inorganic lithium salt and the dispersant is 1% to 10%.

[0013] In one embodiment, in step S100:

[0014] The mass ratio of the graphite oxide, the inorganic lithium salt and the dispersant is 100:(1-5):(0.5-2); and / or,

[0015] The inorganic lithium salt includes at least one of lithium titanate, lithium zirconate, lithium niobate, lithium cerate, and lithium metaaluminate; and / or,

[0016] The dispersant includes at least one of polyvinylbenzenesulfonic acid, polyacrylic acid, and sodium tripolyphosphate; and / or

[0017] The first solvent comprises water; and / or,

[0018] The temperature of the carbonization treatment is 800° C. to 1200° C.; and / or,

[0019] The carbonization treatment time is 1 to 6 hours.

[0020] In one embodiment, after step S100, the method further includes:

[0021] S110, mixing a titanate coupling agent with a second solvent to obtain a second solution, and depositing the titanate coupling agent on the surface of the first precursor material through atomization treatment to obtain a second precursor material.

[0022] In one embodiment, step S200 includes:

[0023] Lithium sulfonate is mixed with an ionic liquid to obtain a third solution, and the second precursor material is dispersed in the third solution. Lithium sulfonate is deposited on the surface of the second precursor material using cyclic voltammetry, and the solution is dried to obtain the negative electrode active material.

[0024] In one embodiment, in step S110:

[0025] In the second solution, the mass proportion of the titanate coupling agent is 1% to 10%; and / or,

[0026] The mass ratio of the titanate coupling agent to the first precursor material is (1-5):100; and / or,

[0027] The titanate coupling agent includes at least one of isopropyl dioleyl (dioctyl phosphate) titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl trioleyl titanate, isopropyl triisostearate titanate and monoalkoxy titanate; and / or,

[0028] The second solvent comprises at least one of benzene, toluene and xylene; and / or,

[0029] The atomization pressure is 0.1KPa to 100KPa; and / or,

[0030] The atomization temperature is 60°C to 130°C.

[0031] In one embodiment, in step S200,

[0032] The mass ratio of the lithium sulfonate, the ionic liquid and the second precursor material is (1-5): (100-500): 100; and / or,

[0033] The ionic liquid includes at least one of 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide, 1-ethyl-3-methylimidazolium perchlorate, and 1-ethyl-3-methylimidazolium p-toluenesulfonate; and / or,

[0034] The voltage range of the cyclic voltammetry is 0.1V to 1.5V; and / or,

[0035] The scan rate of the cyclic voltammetry is 1 mV / s to 5 mV / s; and / or,

[0036] The scanning cycles of the cyclic voltammetry method are 10 to 100.

[0037] The present invention also provides a lithium-ion battery, comprising the negative electrode active material or the negative electrode active material prepared by the negative electrode active material preparation method.

[0038] Lithium ions can be embedded in and extracted from the graphite, thereby realizing the charge and discharge process of the battery. By virtue of the high lithium ion conductivity of the first coating layer composed of inorganic lithium salts, and by virtue of the second coating layer composed of lithium sulfonate, the lithium sulfonate in the second coating layer reduces the direct contact between the graphite and the electrolyte, thereby reducing the interface resistance and improving the charge and discharge efficiency of the battery. Due to its chemical inertness, inorganic lithium salts can effectively resist the erosion of components in the electrolyte, but may cause poor interface contact when used alone. Lithium sulfonate has good electrolyte compatibility and can form a stable SEI film (solid electrolyte interface film), reducing unnecessary side reactions, while also enhancing the adhesion at the interface. The two work together to form an electrolyte / electrode interface that is both stable and efficient, reducing the interface resistance and improving the performance of the lithium battery.

[0039] Furthermore, due to the high thermal stability of inorganic lithium salts, they can maintain structural integrity at high temperatures, preventing irreversible phase transitions or decomposition of the material, thereby improving the battery's performance at high temperatures. The lithium sulfonate layer can maintain a high lithium ion diffusion coefficient at low temperatures, thereby improving the battery's performance at low temperatures. This combination optimizes the lithium ion conduction path under different temperature conditions, improving the battery's rate capability (i.e., its ability to rapidly charge and discharge), and further enhancing the performance of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0041] Figure 1 This is a scanning electron microscope (SEM) image of the graphite composite material in Example 1 provided by the present invention.

[0042] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings and in conjunction with the embodiments. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. Where the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical solutions between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in this field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] Currently, fast-charging graphite is primarily composed of graphite and its outer layer of soft carbon and hard carbon materials. Due to the consumption of lithium ions during the initial charge and discharge process, the initial efficiency of the material and the lithium ion transfer rate are reduced. While there are many ways to improve the fast-charging performance of graphite, such as reducing the particle size and increasing the amount of amorphous carbon coating, these methods will result in a decrease in energy density and a decrease in initial efficiency.

[0045] To this end, in the existing technology, an inorganic lithium layer is arranged on the outside of the graphite, and an organic lithium layer is arranged on the outside of the inorganic lithium layer. The organic lithium layer is a composite organic layer formed by lithium acetate and lithium amide. Although its rate performance is improved, the density deviation of the organic lithium layer and its compatibility with the electrolyte are general, resulting in limited improvement in the fast charging performance of its graphite composite material.

[0046] In order to solve the above technical problems, the present invention also proposes a negative electrode active material, comprising a core, a first coating layer that at least partially covers the core, and a second coating layer that at least covers the first coating layer; wherein the core comprises graphite, the first coating layer comprises an inorganic lithium salt, and the second coating layer comprises lithium sulfonate.

[0047] In the technical solution of the present invention, lithium ions can be embedded in and extracted from the graphite, thereby realizing the charge and discharge process of the battery. By virtue of the high lithium ion conductivity of the first coating layer composed of inorganic lithium salts, and by virtue of the second coating layer composed of lithium sulfonate, the lithium sulfonate in the second coating layer reduces the direct contact between the graphite and the electrolyte, thereby reducing the interface resistance and improving the charge and discharge efficiency of the battery. Due to its chemical inertness, inorganic lithium salts can effectively resist the erosion of components in the electrolyte, but may cause poor interface contact when used alone. Lithium sulfonate has good electrolyte compatibility and can form a stable SEI film (solid electrolyte interface film), reducing unnecessary side reactions, and at the same time enhancing the adhesion at the interface. The two work together to form an electrolyte / electrode interface that is both stable and efficient, reducing the interface resistance and improving the performance of the lithium battery.

[0048] Furthermore, due to the high thermal stability of inorganic lithium salts, they can maintain structural integrity at high temperatures, preventing irreversible phase transitions or decomposition of the material, thereby improving the battery's performance at high temperatures. The lithium sulfonate layer can maintain a high lithium ion diffusion coefficient at low temperatures, thereby improving the battery's performance at low temperatures. This combination optimizes the lithium ion conduction path under different temperature conditions, improving the battery's rate capability (i.e., its ability to rapidly charge and discharge), and further enhancing the performance of the lithium battery.

[0049] In one embodiment, a coupling agent layer is further included, located between the first coating layer and the second coating layer, and the coupling agent layer includes a titanate coupling agent. The titanate coupling agent enhances the bonding strength between the first and second outer shell layers. The titanate coupling agent has amphoteric properties, which can firmly bond the inorganic lithium salt and the lithium sulfonate salt, thereby reducing impedance and increasing tap density.

[0050] The present invention also provides a method for preparing a negative electrode active material, comprising the following steps:

[0051] S100, providing graphite oxide, mixing the graphite oxide, an inorganic lithium salt, a dispersant, and a first solvent, and performing a carbonization treatment to obtain a first precursor material;

[0052] S200. Lithium sulfonate is deposited on the surface of the first precursor material by an electrochemical method to obtain the negative electrode active material; wherein the negative electrode active material includes a core, a first coating layer that at least partially covers the core, and a second coating layer that at least covers the first coating layer; the core includes graphite, the first coating layer includes an inorganic lithium salt, and the second coating layer includes lithium sulfonate.

[0053] By utilizing the hydroxyl carboxyl groups on the surface of graphite oxide to chemically bond with inorganic lithium salts, the structural stability of the material is enhanced. The resulting first coating layer, obtained after carbonization, exhibits advantages such as excellent high-temperature performance and high ion transport. The electrochemical deposition allows the lithium sulfonate to be evenly coated on the surface of the first precursor material, resulting in a uniform and dense second coating layer for the resulting negative electrode active material. This helps ensure the consistency of the material's surface properties, reduces defects and inhomogeneities, increases the material's lithium ion insertion and extraction rate, and improves rate performance.

[0054] In one embodiment, step S100 includes providing graphite oxide, mixing an inorganic lithium salt, a dispersant, and a first solvent to obtain a first solution, dispersing the graphite oxide in the first solution, and carbonizing the solution to obtain a first precursor material; wherein the inorganic lithium salt and dispersant in the first solution account for 1% to 10% by weight. By first forming the first solution, the inorganic lithium salt and dispersant are uniformly distributed in the first solution. When the graphite oxide is dispersed in the first solution, each piece of graphite oxide is uniformly coated with a layer of inorganic lithium salt, which facilitates greater consistency in the thickness and composition of the coating layer and avoids the problem of localized uneven coating, which can cause uneven distribution of the inorganic lithium salt in the first precursor after subsequent carbonization and affect battery performance. Since the inorganic lithium salt and dispersant account for 1% to 10% by weight, this ensures sufficient lithium ion conductivity without compromising the overall physical or chemical stability due to excessive additives.

[0055] In one embodiment, in step S100, the mass ratio of the graphite oxide, the inorganic lithium salt, and the dispersant is 100:(1-5):(0.5-2). Using the above mass ratio can reduce the agglomeration of the graphite oxide and the inorganic lithium salt in the solution, thereby achieving uniform dispersion while controlling the reaction rate between the inorganic lithium salt and the graphite oxide.

[0056] In one embodiment, the inorganic lithium salt includes at least one of lithium titanate, lithium zirconate, lithium niobate, lithium cerate, and lithium metaaluminate. The above components can improve the stability of the chemical bond between the inorganic lithium salt and graphite oxide.

[0057] In one embodiment, the dispersant includes at least one of polyvinylbenzenesulfonic acid, polyacrylic acid, and sodium tripolyphosphate; by using the above dispersant, better mixing and uniform distribution can be achieved between graphite oxide and inorganic lithium salt, which can not only maintain a stable suspension state of the material during the preparation process, but also maintain the structural integrity of the product in subsequent processing steps.

[0058] In one embodiment, the first solvent comprises water. Using water as the first solvent allows the dispersant and inorganic lithium salt to be well dissolved or dispersed in the water, ensuring uniform mixing of the components. Furthermore, water-based systems generally do not require complex solvent recovery systems, simplifying post-processing steps.

[0059] In one embodiment, the carbonization treatment temperature is 800°C to 1200°C. Under a high temperature environment of 800°C to 1200°C, the oxygen-containing functional groups in the graphite oxide undergo decomposition or reduction reactions, gradually restoring a partial graphite structure. This not only helps to improve the conductivity of the material but also its mechanical properties. Furthermore, below 800°C, the degree of reduction of the graphite oxide may be insufficient, and the graphite structure may not be fully restored, affecting the performance of the final material. Exceeding 1200°C may cause excessive carbonization or sintering of the material, destroying the graphite structure and even triggering unnecessary side reactions, reducing the electrochemical activity of the material.

[0060] In one embodiment, the carbonization treatment time is 1 to 6 hours. By setting the carbonization treatment time to 1 to 6 hours, the above-mentioned chemical (graphite oxide is reduced to graphite) and physical changes (the first solvent overflows) can be completed. Less than 1 hour may result in incomplete reaction, while more than 6 hours may cause changes in the material structure or excessive carbonization.

[0061] In one embodiment, after step S100, the process further includes: S110, mixing a titanate coupling agent with a second solvent to obtain a second solution, and depositing the titanate coupling agent on the surface of the first precursor material by atomization to obtain a second precursor material. By atomizing the titanate coupling agent to form a layer of titanate coupling agent (i.e., a coupling agent layer) on the surface of the first precursor material, the stability of the subsequent connection between the second coating layer and the substrate can be improved.

[0062] In one embodiment, step S200 includes: mixing lithium sulfonate with an ionic liquid to obtain a third solution, dispersing the second precursor material in the third solution, depositing lithium sulfonate on the surface of the second precursor material using cyclic voltammetry, and drying to obtain the negative electrode active material. By using cyclic voltammetry to form a second coating layer using the third solution containing lithium sulfonate, this method can ensure high density and good consistency. At the same time, due to the presence of lithium sulfonate, the insertion and extraction rate of lithium ions and the rate performance of the material are also improved. In addition, by setting different voltage scan rates and ranges by cyclic voltammetry, the potential conditions during the deposition process can be precisely controlled, thereby affecting the deposition rate and thickness. It is understandable that the drying can be vacuum drying, which is beneficial to ensuring the performance of the negative electrode active material.

[0063] In one embodiment, in step S110, the titanate coupling agent accounts for 1% to 10% by weight of the second solution. By controlling the weight ratio of the inorganic lithium salt and dispersant to 1% to 10%, this helps ensure that the material has sufficient lithium ion conductivity while not affecting the overall physical or chemical stability due to excessive additives.

[0064] In one embodiment, the mass ratio of the titanate coupling agent to the first precursor material is (1-5) : 100. By using the titanate coupling agent and the first precursor material within the above mass ratio range, the titanate coupling agent can be evenly covered on the surface of the first precursor material.

[0065] In one embodiment, the titanate coupling agent includes at least one of isopropyl dioleyl (dioctyl phosphate) titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl trioleyl titanate, isopropyl triisostearate titanate, and monoalkoxy titanate. The use of the titanate coupling agent with the above components can form an effective bridge between the organic phase and the inorganic phase, thereby enhancing interfacial adhesion.

[0066] In one embodiment, the second solvent includes at least one of benzene, toluene, and xylene. By using the above organic solvent components, the titanate coupling agent can be better dissolved, forming a more uniform and stable solution. The organic solvent is easy to volatilize, which is beneficial for subsequent atomization processing.

[0067] In one embodiment, the atomization pressure is 0.1 KPa to 100 KPa. By setting the atomization pressure to 0.1 KPa to 100 KPa, the titanate coupling agent can form a uniform and dense covering layer on the surface of the first precursor material, thereby improving the interfacial adhesion.

[0068] In one embodiment, the atomization temperature is 60° C. to 130° C. Setting the atomization temperature to 60° C. to 130° C. facilitates the volatilization of the second solvent, allowing the titanate coupling agent to quickly adhere to and evenly distribute on the material surface to form a dense coating.

[0069] In one embodiment, in step S200, the mass ratio of the lithium sulfonate, the ionic liquid, and the second precursor material is (1-5): (100-500): 100. By using the components in the above mass ratio, sufficient lithium sulfonate is provided to improve ion conductivity, promote rapid migration of lithium ions at the electrode / electrolyte interface, and enhance the rate performance of the battery, that is, maintain good charge and discharge efficiency when operating at higher current densities.

[0070] In one embodiment, the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium perchlorate, and 1-ethyl-3-methylimidazolium p-toluenesulfonate. The use of such ionic solutions, which have high ionic conductivity, facilitates improving the speed and efficiency of electrochemical deposition and ensures a uniform and dense deposited layer.

[0071] In one embodiment, the voltage range of the cyclic voltammetry is 0.1 V to 1.5 V. Setting the voltage at 0.1 V to 1.5 V can accelerate ion transport, help form a uniform and dense deposition layer, reduce defects and non-uniformity, and increase deposition rate and thickness.

[0072] In one embodiment, the scan rate of the cyclic voltammetry is 1 mV / s to 5 mV / s. Setting the scan rate within the range of 1 mV / s to 5 mV / s can reduce the effect of overpotential, making the current response closer to equilibrium, allowing more time for migration and deposition, and facilitating the formation of a uniform and dense deposited layer with reduced defects.

[0073] In one embodiment, the number of scan cycles in the cyclic voltammetry method is 10 to 100. By setting the number of scan cycles in the range of 10 to 100, precise control of current, deposition rate, and thickness can be achieved during the electrochemical deposition process.

[0074] In one embodiment, in step S100, the step of providing graphite oxide includes providing graphite and heating the graphite in an oxygen environment to obtain the graphite oxide. The heating in an oxygen environment can generate hydroxyl carboxyl groups on the surface of the graphite, which are suitable for bonding with the inorganic lithium salt.

[0075] In one embodiment, the aerobic environment comprises oxygen and nitrogen. The degree of oxidation can be controlled by adjusting the ratio of oxygen to nitrogen. A higher oxygen ratio accelerates the oxidation reaction but may lead to over-oxidation or structural damage; a lower oxygen ratio slows the reaction, making the oxidation more gentle and controllable.

[0076] In one embodiment, the volume ratio of oxygen to nitrogen in the aerobic environment is (3.5-3): 1. This ratio can balance the speed and depth of the oxidation reaction, ensuring that the graphite surface can be effectively oxidized without causing excessive oxidation or structural damage.

[0077] In one embodiment, the heating temperature is 100° C. to 200° C. Setting the heating temperature between 100° C. and 200° C. in a lower temperature range helps slow down the oxidation reaction rate, making the oxidation process more gentle and controllable, and avoiding violent reactions or damage to the graphite structure that may be caused by high temperature.

[0078] In one embodiment, the heating time is 1 to 3 hours. By setting the heating time to 1 to 3 hours, this time is sufficient for the oxidation reaction to proceed fully while avoiding damage to the graphite structure caused by long-term heating.

[0079] The present invention also provides a lithium-ion battery, comprising the negative electrode active material or the negative electrode active material prepared by the negative electrode active material preparation method.

[0080] The technical solutions of the present invention are further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0081] It should be noted that the graphite oxide used in the following examples was prepared by the following steps:

[0082] Artificial graphite was added to a tubular furnace, and an oxygen mixed gas (volume ratio, oxygen:nitrogen = 10:3, flow rate 500 ml / min) was introduced, then the temperature was raised to 150°C for 2 hours, and then the temperature was cooled to room temperature to obtain graphite oxide.

[0083] Example 1

[0084] A method for preparing a negative electrode active material comprises the following steps:

[0085] 3 g of lithium titanate and 1 g of polyethylene sulfonic acid were added to 80 g of deionized water to prepare a 5 wt% first solution, and then 100 g of graphite oxide was added and dispersed evenly. The mixture was spray-dried and carbonized at 1000° C. for 3 h to obtain a first precursor material.

[0086] 3 g of isopropyl dioleyl (dioctyl phosphate) titanate was added to 100 g of toluene organic solvent to prepare a 3 wt% second solution, and then 100 g of the first precursor material was used as a substrate and transferred to a three-necked flask by atomization. The second solution was used as an atomizing gas at an atomizing pressure of 50 kPa and an atomizing temperature of 90 ° C. A titanate coupling agent was deposited on the surface of the substrate to obtain a second precursor material;

[0087] 3 g of lithium sulfonate was added to 300 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt to prepare a third solution, and then 100 g of the second precursor material was added and dispersed evenly. The solution was electrochemically deposited using cyclic voltammetry in a voltage range of 0.1-1.5 V, a scan rate of 2 mV / s, and scanned for 50 cycles to deposit lithium sulfonate on the surface of the second precursor material. The solution was then vacuum dried at 150 ° C for 24 h to obtain a negative electrode active material.

[0088] Example 2

[0089] A method for preparing a negative electrode active material comprises the following steps:

[0090] 1g of lithium zirconate and 0.5g of polyacrylic acid were added to 150g of deionized water to prepare a 1wt% first solution, and then 100g of graphite oxide was added and dispersed evenly. The mixture was spray-dried and carbonized at 800°C for 6h to obtain a first precursor material.

[0091] 1g of isopropyl tri(dioctylphosphoyloxy) titanate was added to 100g of benzene organic solvent to prepare a 1wt% second solution, and then 100g of the first precursor material was used as a substrate and transferred to a three-necked flask by atomization. The second solution was used as an atomizing gas at an atomizing pressure of 0.1KPa and an atomizing temperature of 60°C to deposit a titanate coupling agent on the surface of the substrate to obtain a second precursor material;

[0092] 1 g of lithium sulfonate was added to 100 g of 1-ethyl-3-methylimidazole perchlorate to prepare a third solution, and then 100 g of the second precursor material was added and dispersed evenly. The solution was electrochemically deposited using cyclic voltammetry in a voltage range of 0.1-1.5 V and a scan rate of 1 mV / s for 10 weeks to deposit lithium sulfonate on the surface of the second precursor material. The solution was then vacuum dried at 150°C for 24 hours to obtain a negative electrode active material.

[0093] Example 3

[0094] A method for preparing a negative electrode active material comprises the following steps:

[0095] 5 g of lithium niobate and 2 g of sodium tripolyphosphate were added to 70 g of deionized water to prepare a 10 wt% first solution, and then 100 g of graphite oxide was added and dispersed evenly. The mixture was spray-dried and carbonized at 1200° C. for 1 h to obtain a first precursor material.

[0096] 5 g of isopropyl trioleyl titanate was added to 50 g of xylene organic solvent to prepare a 10 wt% second solution. Then, 100 g of the first precursor material was used as a substrate and transferred to a three-necked flask by atomization. The second solution was used as an atomizing gas. The atomizing pressure was 100 kPa and the atomizing temperature was 130 ° C. A titanate coupling agent was deposited on the surface of the substrate to obtain a second precursor material.

[0097] 5 g of lithium sulfonate was added to 500 g of 1-ethyl-3-methylimidazole toluenesulfonate to prepare a third solution, and then 100 g of the second precursor material was added and dispersed evenly. The solution was electrochemically deposited using cyclic voltammetry in a voltage range of 0.1-1.5 V, a scan rate of 5 mV / s, and 100 scans. Lithium sulfonate was deposited on the surface of the second precursor material and vacuum dried at 150 ° C for 24 h to obtain a negative electrode active material.

[0098] Comparative Example 1

[0099] Compared with Example 1, Comparative Example 1 omitted all steps after obtaining the first precursor material, and the rest were the same as Example 1.

[0100] Comparative Example 2

[0101] Compared with Example 1, Comparative Example 2 is the same as Example 1 except that the first precursor material is replaced with graphite.

[0102] Performance Testing

[0103] 1. Negative electrode active material morphology test

[0104] The negative electrode active material prepared in Example 1 was tested by scanning electron microscopy (SEM), and the results were as follows: Figure 1shown.

[0105] Depend on Figure 1 It can be seen that the negative electrode active material particles present a lithium sulfonate / inorganic lithium salt double-coated graphite composite material structure, a reasonable size distribution, and a particle size D50 between 10-15 μm.

[0106] 2. Button Battery Test

[0107] The negative electrode active materials obtained in Examples 1-3 and Comparative Examples 1-2 were assembled into button-type batteries.

[0108] The specific preparation method is:

[0109] A binder, a conductive agent, and a solvent were added to the negative electrode active material, stirred to form a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet. The binder used was PVDF, the conductive agent was conductive carbon black (SP), and the solvent was N-methylpyrrolidone (NMP). The ratio of the negative electrode active material, SP, PVDF, and NMP was 95g:1g:4g:220mL. The electrolyte used LiPF6 as the electrolyte salt and a mixture of EC and DEC with a volume ratio of 1:1 as the solvent. The metal lithium sheet was the counter electrode, and the separator was a polypropylene (PP) film. The button cell was assembled in an argon-filled glove box. The electrochemical performance was carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V-2.0V and a charge and discharge rate of 0.1C. The rate (2C / 0.1C) was also tested, and the test results are shown in Table 1.

[0110] At the same time, the specific surface area of ​​the above-mentioned negative electrode active material was tested in accordance with the national standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", the diffusion coefficient of the material was tested by GITT, and the powder resistance was tested by a four-probe tester. The test results are shown in Table 1.

[0111] Table 1

[0112]

[0113]

[0114] Table 1 shows that the negative electrode active materials prepared in Examples 1 to 3 have higher specific surface areas and diffusion coefficients than those prepared in Comparative Examples 1 to 2, while their powder resistivity is lower. Coin-type batteries prepared using the negative electrode active materials prepared in Examples 1 to 3 exhibit higher initial discharge specific capacity, initial efficiency, and rate capability than those prepared using the negative electrode active materials prepared in Comparative Examples 1 to 2. This indicates that coating the graphite surface with inorganic lithium salts and lithium sulfonates not only improves the ion diffusion coefficient and rate capability of the negative electrode active materials, but also reduces irreversible capacity and improves initial discharge efficiency. Furthermore, this coating method increases the specific surface area of ​​the negative electrode active material and reduces powder resistivity, thereby enhancing the migration rate of lithium ions within the negative electrode active material.

[0115] 3. Soft pack battery test

[0116] The negative electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were used to prepare negative electrode sheets. 0.6 Co 0.2 Mn 0.2 )O2) is the positive electrode material; LiPF6 is the electrolyte salt in the electrolyte, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 is used as the solvent; Celgard2400 membrane is used as the separator to prepare 5Ah soft-pack batteries, which are marked as C1, C2, C3 and D1, D2.

[0117] (1) Liquid absorption capacity test

[0118] Use a 1mL burette and draw electrolyte VmL, add one drop on the surface of the negative electrode, and time until the electrolyte is completely absorbed. Record the time t. The test results are shown in Table 2.

[0119] (2) Electrode surface resistance test

[0120] Use the membrane resistance tester to test the negative electrode (size 100cm 2 ) The resistance test was performed using a pressure of 50 kN, and the surface resistance of the electrode was calculated. The test results are shown in Table 2.

[0121] (3) Rate performance test

[0122] Rate performance test: The charge and discharge voltage range is 2.8~4.2V, the test temperature is 25±3.0℃, and the charging is performed at 1.0C, 2.0C, 3.0C, and 5.0C, and the discharge is performed at 1.0C. The constant current ratio and temperature of the battery are tested under different charging modes. The test results are shown in Table 3.

[0123] Table 2

[0124]

[0125]

[0126] As can be seen from Table 2, the liquid absorption rates of the negative electrode active materials prepared in Examples 1 to 3 are lower than those of the negative electrode active materials prepared in Comparative Examples 1 to 2; and the electrode sheet sheet resistance of the negative electrode active materials prepared in Examples 1 to 3 is lower than that of the negative electrode active materials prepared in Comparative Examples 1 to 2. This is because the materials in Examples 1-3 have a high specific surface area, shortening the liquid absorption time, and a low powder resistivity, thereby reducing the electrode sheet sheet resistance.

[0127] Table 3

[0128]

[0129] As can be seen from Table 3, the rate performance of batteries prepared using the negative electrode active materials prepared in Examples 1 to 3 is higher than that of batteries prepared using the negative electrode active materials prepared in Comparative Examples 1 to 2. This is because the inorganic lithium salt and lithium sulfonate coating in the negative electrode active materials prepared in Examples 1 to 3 increases the diffusion coefficient of lithium ions and reduces the powder resistivity, thereby improving the constant current ratio under different rate conditions and reducing the temperature rise.

[0130] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Those skilled in the art will readily appreciate that the present invention is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of the present invention.

Claims

1. A negative electrode active material, characterized in that: It comprises an inner core, a first coating layer at least partially covering the inner core, and a second coating layer at least covering the first coating layer; wherein the inner core comprises graphite, the first coating layer comprises an inorganic lithium salt, and the second coating layer comprises lithium sulfonate.

2. The negative electrode active material according to claim 1, characterized in that The invention also comprises a coupling agent layer, wherein the coupling agent layer is located between the first coating layer and the second coating layer, and the coupling agent layer comprises a titanate coupling agent.

3. A method for preparing a negative electrode active material, characterized in that: The following steps are involved: S100, providing graphite oxide, mixing the graphite oxide, an inorganic lithium salt, a dispersant and a first solvent, and performing a carbonization treatment to obtain a first precursor material; S200, depositing lithium sulfonate on the surface of the first precursor material by an electrochemical method to obtain the negative electrode active material; The negative electrode active material includes a core, a first coating layer at least partially coating the core, and a second coating layer at least coating the first coating layer; the core includes graphite, the first coating layer includes an inorganic lithium salt, and the second coating layer includes lithium sulfonate.

4. The method for preparing the negative electrode active material according to claim 3, characterized in that: Step S100 includes: Providing graphite oxide, mixing an inorganic lithium salt, a dispersant and a first solvent to obtain a first solution, dispersing the graphite oxide in the first solution, and performing a carbonization treatment to obtain a first precursor material; Wherein, in the first solution, the mass proportion of the inorganic lithium salt and the dispersant is 1% to 10%.

5. The method for preparing the negative electrode active material according to claim 3, characterized in that: In step S100: The mass ratio of the graphite oxide, the inorganic lithium salt and the dispersant is 100:(1-5):(0.5-2); and / or, The inorganic lithium salt includes at least one of lithium titanate, lithium zirconate, lithium niobate, lithium ceria, and lithium aluminate; and / or, The dispersant comprises at least one of polyvinylbenzenesulfonic acid, polyacrylic acid and sodium tripolyphosphate; and / or, The first solvent comprises water; and / or, The temperature of the carbonization treatment is 800°C to 1200°C; and / or, The carbonization treatment time is 1 to 6 hours.

6. The method for preparing the negative electrode active material according to claim 3, characterized in that: After step S100, the method further includes: S110, mixing a titanate coupling agent with a second solvent to obtain a second solution, and depositing the titanate coupling agent on the surface of the first precursor material through atomization to obtain a second precursor material.

7. The method for preparing the negative electrode active material according to claim 6, characterized in that: Step S200 includes: Lithium sulfonate is mixed with an ionic liquid to obtain a third solution, and the second precursor material is dispersed in the third solution. Lithium sulfonate is deposited on the surface of the second precursor material using cyclic voltammetry, and the solution is dried to obtain the negative electrode active material.

8. The method for preparing the negative electrode active material according to claim 6, characterized in that: In step S110: In the second solution, the mass proportion of the titanate coupling agent is 1% to 10%; and / or, The mass ratio of the titanate coupling agent to the first precursor material is (1-5):100; and / or, The titanate coupling agent includes at least one of isopropyl dioleyl (dioctyl phosphate) titanate, isopropyl tri (dioctyl phosphate) titanate, isopropyl trioleyl titanate, isopropyl triisostearate titanate and monoalkoxy titanate; and / or, The second solvent comprises at least one of benzene, toluene and xylene; and / or, The atomization pressure is 0.1 KPa to 100 KPa; and / or, The atomization temperature is 60°C to 130°C.

9. The method for preparing the negative electrode active material according to claim 4, characterized in that: In step S200, The mass ratio of the lithium sulfonate, the ionic liquid and the second precursor material is (1-5): (100-500): 100; and / or, The ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt, 1-ethyl-3-methylimidazolium perchlorate and 1-ethyl-3-methylimidazolium p-toluenesulfonate; and / or, The voltage range of the cyclic voltammetry is 0.1V to 1.5V; and / or, The scanning rate of the cyclic voltammetry is 1 mV / s to 5 mV / s; and / or, The scanning cycles of the cyclic voltammetry method are 10 to 100.

10. A lithium ion battery, characterized in that: The negative electrode active material is prepared by the negative electrode active material as claimed in claim 1 or 2 or the method for preparing the negative electrode active material as claimed in any one of claims 3 to 9.

Citation Information

Patent Citations

  • Lithium ion batteries cathode material additive, preparation method thereof, and cathode material and lithium ion battery both containing same

    CN105098188A

  • Lithium ion battery with high energy density

    CN106960949A

  • Graphite composite electrode material and preparation method thereof

    CN113675389A

  • Modified artificial graphite negative electrode material and preparation method thereof

    CN118198325A

  • Artificial graphite composite material for energy storage battery as well as preparation method and application of artificial graphite composite material

    CN118448600A

Cited By

  • Negative electrode material, preparation method thereof and secondary battery

    CN120581556A